Εndovascular Repair of Extracranial Carotid Artery Aneurysms: A Systematic Review. (April 2020) - Giannopoulos, Stefanos; Trinidad, Evan; Aronow, Herbert; Soukas, Peter; Armstrong, Ehrin J.
Objective: Both true and false extracranial carotid artery aneurysms (ECAA) are a potential source of morbidity and mortality. While ECAA have historically been treated surgically, endovascular reconstruction with stenting is an emerging treatment option. The aim of our study was to report clinical/radiologic outcomes following endovascular repair of ECAAs. Methods: A comprehensive systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. Results: A total of 68 case reports and case series, comprising 162 patients, were included. Most patients presented with at least one symptom or sign related to the ECAA (89.5%; N = 145/162). In 42.6% (N = 69/162) and 46.3% (N = 75/162) of the cases polytetrafluoroethylene covered and uncovered stents were deployed respectively. Immediate post-procedural imaging demonstrated complete aneurysm exclusion in 86.4% (N = 140/162) of the cases and minimal filling of the aneurysm sack in 10.5% (N = 17/162) of all cases. Perioperative adverse event rates were 3.1% for stroke, 1.2% for transient ischemic attack (TIA) and 4.3% for mortality. During a mean follow-up of 21.8months, there were additionally observed one stroke, two TIAs and three deaths. Overall 88.6 % of the patients (N = 117/132) remained asymptomatic, partially recovered or at least did not suffer from new neurologic deficits during follow up, with no signs of stenosis or occlusion of the carotid artery. Conclusions: Endovascular stenting for the treatment of ECAAs is feasible with acceptable short- and long-term clinical and radiologic outcomes. Prospective real-world studies are needed to further validate the safety and the long-term patency of endovascular repair.